Estrategias pedagógicas cualificadoras de procesos lectores en los estudiantes de quinto "C" grado de la institución educativa técnica Juan XXIII de Malambo (2008)
This investigation Work have an introductory part and four chapters. Describes on the next text INTRODUCTION. Here are desribed student’s difficults of five degree of primary basic of the “Institución Educativa Técnica Juan XXIII de Malambo” to understand a significative reader process, that is, a comprehensive reader process that involve learning. Immediately formulated a question, this question, express the problem. Justification and the objectives of the investigation work are expressed in this introduction. CHAPTER 2. It’s denominated “Reference frame” or “art state”. In this chapter, it was analyzed the antecedents, the legal frame, the theoric frame of the problem. The base of the ideas are theories acepted by the international scientific community. At lest was elaborated a conceptual frame with claves words of the investigation. CHAPTER 3. Denominate “Mhetodologycal” design. In this chapter is explained and argueded the paradigm investigation, type investigation, line investigation, categories investigation and the instruments will apply to objective people. CHAPTER 4. Is the disgnostic of the reality, it contain analisys and interpretation of tecnics and instruments applyed to objective people. CHAPTER 5. In this chapter are expressed conclusions and recommendations,it will be base by proposal. CHAPTER 6. Present design and components of the proposal “Formando buenos lectores”. This proposal is an alternative of solution problem establishment. Action plan has strategies of the proposal